Pengaruh Layanan Konseling Kelompok Dengan Teknik Relaksasi Terhadap Stres Akademik Siswa SMAN 99 Jakarta - Dhea Puspitasari; Asni Asni (Journal on Education, 2024)
This study's title is "The Effect of Group Counselling Services with Relaxation Techniques on the Academic Stress of Students at SMAN 99 Jakarta" . This project aims to provide class XI students at SMAN 99 Jakarta with group counselling services that include relaxation methods in order to lower their academic stress levels. The study took place from October to May and used a purposive sample of ten students from a population of thirty-six to administer a one-group pretest-posttest. For the academic stress variable, the data collecting tool relied on a questionnaire with a reliability of 0.867 and 40 valid statements out of 52. The data is normally distributed, according to the normalcy test, and the hypothesis testing using Paired-Samples With a p-value of 0.000 < 0.05 as shown by the T-Test, the null hypothesis (Ha) is accepted. As a consequence of participating in group counselling sessions that included relaxation methods, students at SMAN 99 Jakarta reported less academic stress.